2015
DOI: 10.1016/j.jacc.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Clinical Pharmacist in the Care of Patients With Cardiovascular Disease

Abstract: Team-based cardiovascular care, including the use of clinical pharmacists, can efficiently deliver high-quality care. This Joint Council Perspectives paper from the Cardiovascular Team and Prevention Councils of the American College of Cardiology provides background information on the clinical pharmacist's role, training, certification, and potential utilization in a variety of practice models. Selected systematic reviews and meta-analyses, highlighting the benefit of clinical pharmacy services, are summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 47 publications
2
130
0
1
Order By: Relevance
“…In line with the previously addressed need to adjust the existing care model so that where technicians can ‘free up’ the pharmacists’ time, participants mentioned that pharmacy technicians could be very instrumental in identifying patients who potentially might benefit from additional counselling. This is congruent with the recent calls for enhancing the roles of pharmacy technicians, so that the pharmacists can focus more on clinical and counselling aspects, rather than dispensing . Having a dedicated pharmacist in store, who would be in charge of this additional service (similar to the provision of medication management services) was acknowledged as a facilitating factor.…”
Section: Discussionsupporting
confidence: 56%
“…In line with the previously addressed need to adjust the existing care model so that where technicians can ‘free up’ the pharmacists’ time, participants mentioned that pharmacy technicians could be very instrumental in identifying patients who potentially might benefit from additional counselling. This is congruent with the recent calls for enhancing the roles of pharmacy technicians, so that the pharmacists can focus more on clinical and counselling aspects, rather than dispensing . Having a dedicated pharmacist in store, who would be in charge of this additional service (similar to the provision of medication management services) was acknowledged as a facilitating factor.…”
Section: Discussionsupporting
confidence: 56%
“…Within a given delivery system, physician and caregiver skills are thought to be important in developing supportive patient relationships. Studies have shown that team-based care, in which physician extenders, pharmacists, and nursing team members are engaged in patient education and monitoring of adherence, can be effective in improving adherence and health outcomes (22,23). The role of the pharmacist is critical in the post-hospital setting.…”
Section: Key Factors Affecting Adherencementioning
confidence: 99%
“…FDA-mediated patient engagement across the health care continuum directly addresses a key issue (i.e., patient engagement and education) that was shown to improve medication adherence (22,23). Feedback from the patient’s perspective may help FDA policies to evolve regarding drug development by addressing patient concerns and thus increasing the likelihood of medication adherence.…”
Section: Specific Fda Activitiesmentioning
confidence: 99%
“…The American Heart Association endorses chronic care management models with multidisciplinary care involving a clinical pharmacist for patients with cardiovascular disease . The presence of a pharmacist in clinic settings has been shown to improve management of diabetes and hypertension, rates of tobacco cessation and appropriate immunizations, and medication adherence and patient medication knowledge . While a cardiology clinic pharmacist would be expected to assist with medication management related to patients' cardiovascular concerns, these studies demonstrate that pharmacists can also improve the management of other chronic conditions.…”
Section: Discussionmentioning
confidence: 99%